NLRC3 High Expression Represents a Novel Predictor for Positive Overall Survival Correlated With CCL5 and CXCL9 in HCC Patients - Wang, Chengpan; Shi, Jieyi; Xu, Jietian; Fu, Qiaoyu; Ding, Youpeng; Yang, Jessie; Liu, Binbin; Gao, Qiang; Qin, Jie; Liang, Chunmin (Frontiers in Oncology, 2022)
NLRC3 (NLR family caspase recruitment domain containing 3) has been reported as a factor of inhibiting inflammatory responses. It's role in hepatocellular carcinoma (HCC) is still unknown. In this study we firstly used the Gene Expression Omnibus (GEO) database and multiple immunohistochemical analysis (mIHC) with tumor tissue microarrays (TMAs) of HCC patients to evaluate NLRC3 levels. The tumor-bearing mouse models were also established with NLRC3 over-expressing and knock-down Hepal-6 cells to assess its effect. The data shown high NLRC3 expression was related with favorable overall survival (P=0.0386) and disease-free survival (P=0.0458). In addition, NLRC3 expression showed a positive correlation between CD8+ T cells infiltration. In vivo, NLRC3-overexpressing Hepal-6 tumors showed increased CD8+ T cell infiltration. NLRC3-knockdown Hepa1-6 tumors displayed decreased CD8+ T cell infiltration. At the same time, we also found the positive correlations between NLRC3 and C-C motif chemokine ligand 5 (CCL5, P<0.0001, R2=0.2372) as well as C-X-C motif chemokine ligand 9 (CXCL9, P<0.0001, R2=0.2338) expressions. So NLRC3 high expression represents a novel predictor for positive survival outcomes in HCC patients, and NLRC3 is involved in CD8+ T cell infiltration, which is correlated with increased CCL5 and CXCL9 in tumor microenvironment (TME). This study implies that boosting NLRC3 is a promising treatment to enhance survival in HCC patients.